Toxoplasma gondii infection and food consumption: A systematic review and meta-analysis of case-controlled studies. Issue 18 (12th December 2018) - Belluco, Simone; Simonato, Giulia; Mancin, Marzia; Pietrobelli, Mario; Ricci, Antonia
ABSTRACT: Background : Toxoplasmosis is a zoonotic disease causing severe symptoms in pregnant women and immunocompromised individuals. On average, worldwide, around 30% of people are seropositive. The oral transmission route is of great significance and food, particularly meat, is an important transmission vehicle for T. gondii . However, the role of different food matrices is debated. Objectives : The aim of this review was to assess the risk of humans developing acute T. gondii infection via the foodborne route. Study eligibility criteria : Case-control studies including acute cases of T. gondii infection were included after literature searches, without time limits, in several databases. All studies estimating the risk of acquiring T. gondii infection after consumption of specific food categories were included. Results : Three risk factors proved to be significantly associated with acute T. gondii infection in humans: consumption of raw/undercooked meat, Odds Ratio (OR) 3.44 (1.29–9.16), consumption of raw/undercooked beef, OR 2.22 (1.57–3.12), and consumption of raw/undercooked sheep meat, OR 3.85 (1.85–8.00). Consumption of raw/undercooked pork, raw eggs, and unpasteurized milk proved to be non-significant risk factors. Limitations : Limitations in the present review and meta-analysis are due to the low number of case-control studies available for analysis and the lack of a search strategy targeting gray literature. Conclusion : Consumption of raw/undercooked beef and sheep meat are important risk factors for T. gondii infection. Their consumption should be avoided in order to prevent toxoplasmosis, particularly by those in at-risk categories, including pregnant women. The review protocol is registered in PROSPERO database (CRD42016043295).